How T cells recognize lipids as antigens. (April 2009) - De Libero, Gennaro
T lymphocytes recognize lipid antigens as complexes formed by lipids with CD1 antigen-presenting molecules. These complexes are formed within antigen-presenting cells after lipid internalization and their stability contributes to lipid immunogenicity. Immunogenic lipids are amphiphatic structures that insert the hydrophobic tails within the antigen-binding pockets of CD1 molecules and leave their hydrophilic moieties exposed for interaction with T-cell receptors. Minimal variations in both parts influence T-cell recognition, which demonstrates a high grade of specificity. Presentation of lipid antigens requires their efficient internalization, traffic to endosomal compartments where CD1 molecules are encountered, extraction from the membrane, and insertion into CD1 lipid-binding pockets. This article reviews how these events occur and how they are regulated.